1996
DOI: 10.3354/meps137203
|View full text |Cite
|
Sign up to set email alerts
|

Growth and population dynamics of Posidonia oceanica on the Spanish Mediterranean coast:elucidating seagrass decline

Abstract: The growth and population dynamics of Posidonia oceanica were examined in 29 meadows along 1000 km of the Spanish Mediterranean coast (from 36"46' to 42"22' N). oceanica developed the densest meadows (1141 shoots m-') and the highest aboveground biomass (1400 g DW m") between 38 and 39"N. P. oceanica shoots produced, on average, 1 leaf every 47 d , though leaf formation rates in the populations increased from north to south (range 5 7 to 8 . 9 leaves shoot-' yr-'). P oceanica is a long-living seagrass, with sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
149
2
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(160 citation statements)
references
References 11 publications
6
149
2
3
Order By: Relevance
“…The temporal growth pattern of total biomass, biomass of leaves, flowers and biomass of roots and rhi-zomes of Zostera novazelandica (Ramage & Schiel 1998) show the same unimodal seasonal curves reported for Z. noltii (Vermaat et al 1987, PerezLlorens & Niell 1993), Z. manna (McRoy 1970, SandJensen 1975, Jacobs 1979, Nienhuis & De Bree 1980, and Thalassia testudinum (Lee & Dunton 1996) although this can vary considerably among years (Marba et al 1996a, Mellors et al 1993. Total biomass increases concurrently with the production of reproductive shoots (Kraemer & Alberte 1993) and is associated with increased temperature and irradiance (Dunton 1994, Lee & Dunton 1996.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The temporal growth pattern of total biomass, biomass of leaves, flowers and biomass of roots and rhi-zomes of Zostera novazelandica (Ramage & Schiel 1998) show the same unimodal seasonal curves reported for Z. noltii (Vermaat et al 1987, PerezLlorens & Niell 1993), Z. manna (McRoy 1970, SandJensen 1975, Jacobs 1979, Nienhuis & De Bree 1980, and Thalassia testudinum (Lee & Dunton 1996) although this can vary considerably among years (Marba et al 1996a, Mellors et al 1993. Total biomass increases concurrently with the production of reproductive shoots (Kraemer & Alberte 1993) and is associated with increased temperature and irradiance (Dunton 1994, Lee & Dunton 1996.…”
Section: Discussionmentioning
confidence: 70%
“…Perturbations in seagrass communities have resulted from pollution (Cambridge & McComb 1984), erosion (Kirkman 1978) and storm activity which vary considerably in scale (Clarke & Kirkman 1989). Northern hemisphere populations have suffered severely reduced abundances due to increased coastal development and anthropogenic eutrophication, and other environmental changes (McComb et al 1981, Short & Wyllie-Echeverria 1996, Marba et al 1996a. Although decline has occurred almost worldwide (Cambridge 1975, Kemp et al 1983, Larkum & West 1983, Cambridge & McComb 1984, studies of the dynamics of seagrass cover and the associated colonisation, expansion, recession and mortality processes are few.…”
Section: Introductionmentioning
confidence: 99%
“…Mediterranean seagrass meadows, particularly those of the endemic species Posidonia oceanica, are experiencing widespread decline (Marba et al 1996(Marba et al , 2005Peirano et al 2005) due to a combination of direct anthropogenic pressure and climate change (Sánchez-Jerez and Ramos Esplá 1996; Balestri et al 2004;Pergent-Martini et al 2006). This decline is offering scope for opportunistic and exotic species to invade these habitats.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in morphology, growth rate, leaf length and density mainly occur at small spatial scales (Balestri et al, 2003;Borg et al, 2005;Zupo et al, 2006b). Under disturbances, Marbà et al (1996) reported a shoot recruitment rate of P. oceanica that was lower than the mortality rate, thus leading to a slowly decreasing shoot density.…”
Section: Available Literature On Posidonia Oceanica Seascape Ecologymentioning
confidence: 99%